Stimuler l'optimisme et renforcer les capacités des femmes entrepreneures: leçons apprises de la COVID-19. (3rd September 2022) - Saba, Tania; Danthine, Éléonore; Registre, Jean Frantz Ricardeau; Cachat-Rosset, Gaëlle
Abstract: While government, institutional and community efforts were in full swing to stimulate women's entrepreneurship, COVID-19 hit the global economy hard. This article focuses on the determinants that stimulate the entrepreneurial optimism among women entrepreneurs and strengthen the capacity of Quebec's SMEs to survive. Explanatory frameworks from chaos and dynamic capacities theories are mobilized to study how entrepreneurial skills and financial needs shape women's entrepreneurial optimism, which in turn determines the resilience of SMEs in times of crisis. The study is based on a survey of 1, 080 female entrepreneurs conducted in April 2020. The results highlight the need for business skill building, innovation skill development and new digital skills to boost entrepreneurial optimism and increase the chances of surviving the crisis. On the other hand, despite targeted government assistance, difficulties in accessing financing remain and high debt levels are major obstacles to overcoming the crisis.